2014
DOI: 10.2343/geochemj.2.0316
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical characteristics of meltwater and pondwater on Barton and Weaver Peninsulas of King George Island, West Antarctica

Abstract: In Antarctica, the geochemical properties of meltwater and pondwater are very sensitive to global warming. Therefore, understanding the geochemical properties of the meltwater and pondwater is crucial to evaluating global climate change. This study was performed to examine the chemical and isotopic compositions of the meltwater and pondwater at the Barton and Weaver Peninsulas of King George Island, Antarctica, to understand their spatial variation and to evaluate factors controlling the surface water chemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Not only seasonal, but also fluctuating variation in water properties, which is prominent in the intertidal zone, has affected N. concinna for a long time [37]. Especially the meltwater which inflows to Marian Cove is acidic, because the King George Island is volcanic Island [15]. Therefore, the meltwater in Marian Cove has a low pH level in summer season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only seasonal, but also fluctuating variation in water properties, which is prominent in the intertidal zone, has affected N. concinna for a long time [37]. Especially the meltwater which inflows to Marian Cove is acidic, because the King George Island is volcanic Island [15]. Therefore, the meltwater in Marian Cove has a low pH level in summer season.…”
Section: Discussionmentioning
confidence: 99%
“…Freshwater streams and ponds are also developed from the surrounding snow field in summer, and a substantial amount of fresh water is introduced into the cove. The meltwater stream and pond water of Baton Peninsula and Weaver Peninsula, between which Marian Cove is located, has relatively lower pH ranges (meltwater: <4.38, pond water: <5.00), because King George Island is a volcanic island [15]. As a result, the surface water in Marian Cove has a distinct salinity gradient along the distance from the glacier during the austral summer months [16].…”
Section: Introductionmentioning
confidence: 99%
“…South-western maritime areas of the Barton Peninsula are ice-free during the summer season. Melt and pond waters, which are habitats for aquatic organisms, are concentrated in the coastal area (Lim et al 2014).…”
Section: Site Description and Methodsmentioning
confidence: 99%
“…Detailed descriptions of the study area are given in previous studies (e.g., Lee et al, 2004;Lim et al, 2014;Choi et al, 2022). In short, its surface area is approximately 1,310 km 2 and its 92% is covered with glaciers with a maximum thickness of 395 m. The snow cover depth ranges from 2 to 73 cm, and mainly melts in summer (November-March; Jiahong et al, 1998).…”
Section: Study Areamentioning
confidence: 99%
“…The Barton Peninsula of King George Island, which is the focus of this study, is located in the marginal area of West Antarctica, where climate is warmer and more humid than in other parts of Antarctica (e.g., Campbell and Claridge, 1987), and will be much more sensitive to increasing global surface temperatures. Although previous studies have suggested little chemical weathering occurs in the Barton Peninsula (Lee et al, 2004;Santos et al, 2007), recent studies have indicated that chemical weathering may affect to some extent the water chemistry and soil formation (Lim et al, 2014;Lopes et al, 2019;Lopes et al, 2021).…”
Section: Introductionmentioning
confidence: 96%